Intravenous versus inhalational techniques for rapid emergence from anaesthesia in patients undergoing brain tumour surgery: A Cochrane systematic review - Hemanshu Prabhakar; Gyaninder P. Singh; Charu Mahajan; Indu Kapoor; Mani Kalaivani; Vidhu Anand (Journal of Neuroanaesthesiology and Critical Care, 2017)
Background: Early and rapid emergence from anaesthesia is desirable for most neurosurgical patients. With the availability of newer intravenous and inhalational anaesthetic agents, all of which have inherent advantages and disadvantages, we remain uncertain as to which technique may result in more rapid early recovery from anaesthesia. The objective of this review was to assess the effects of intravenous versus inhalational techniques for rapid emergence from anaesthesia in patients undergoing brain tumour surgery. Methods: We searched the Cochrane Central Register of Controlled Trials (CENTRAL; 2014, Issue 6) in The Cochrane Library, MEDLINE via Ovid SP (1966 to June 2014) and EMBASE via Ovid SP (1980 to June 2014). We also searched specific websites, such as www.indmed.nic.in, www.cochrane-sadcct. org and www.clinicaltrials.gov (October 2014). We included randomised controlled trials (RCTs) that compared the use of intravenous anaesthetic agents such as propofol and thiopentone with inhalational anaesthetic agents such as isoflurane and sevoflurane for maintenance of general anaesthesia during brain tumour surgery. Primary outcomes were emergence from anaesthesia (assessed by time to follow verbal commands, in minutes) and adverse events during emergence, such as haemodynamic changes, agitation, desaturation, muscle weakness, nausea and vomiting, shivering and pain. Secondary outcomes were time to eye opening, recovery from anaesthesia using the Aldrete or modified Aldrete score (i.e., time to attain score ≥9, in minutes), opioid consumption, brain relaxation (as assessed by the surgeon on a 4- or 5-point scale) and complications of anaesthetic techniques, such as intraoperative haemodynamic instability in terms of hypotension or hypertension (mmHg), increased or decreased heart rate (beats/min) and brain swelling. We used standardised methods in conducting the systematic review, as described by the Cochrane Handbook for Systematic Reviews of Interventions. We used a fixed-effect model when we found no evidence of significant heterogeneity between studies, and a random-effects model when heterogeneity was likely. Results: We included 15 RCTs with 1833 participants. We determined that none of the RCTs were of high methodological quality. For our primary outcomes, pooled results from two trials suggest that time to emergence from anaesthesia, that is, time needed to follow verbal commands, was longer with isoflurane than with propofol (mean difference [MD] –3.29 min, 95% confidence interval [CI] –5.41––1.18, low-quality evidence), and time to emergence from anaesthesia was not different with sevoflurane compared with propofol (MD 0.28 min slower with sevoflurane, 95% CI – 0.56–1.12, four studies, low-quality evidence). Pooled analyses for adverse events suggest lower risk of nausea and vomiting with propofol than with sevoflurane (risk ratio [RR] 0.68, 95% CI 0.51–0.91, low-quality evidence) or isoflurane (RR 0.45, 95% CI 0.26–0.78) and greater risk of haemodynamic changes with propofol than with sevoflurane (RR 1.85, 95% CI 1.07–3.17), but no differences in the risk of shivering or pain. Pooled analyses for brain relaxation suggest lower risk of tense brain with propofol than with isoflurane (RR 0.88, 95% CI 0.67–1.17, low-quality evidence), but no difference when propofol is compared with sevoflurane. Conclusions: The finding of our review is that the intravenous technique is comparable with the inhalational technique of using sevoflurane to provide early emergence from anaesthesia. Adverse events with both techniques are also comparable. However, we derived evidence of low quality from a limited number of studies. The use of isoflurane delays emergence from anaesthesia. These results should be interpreted with caution. RCTs based on uniform and standard methods are needed.